The Silent Patient - Ibrahim Shah (london Orion, 1977)
"Alicia Berenson's life is seemingly perfect. A famous painter married to an in-demand fashion photographer, she lives in a grand house overlooking a park in one of London's most desirable areas. One evening, her husband, Gabriel, returns home late from work, and Alicia shoots him five times in the face and then never speaks another word. Alicia's refusal to talk, or give any kind of explanation, turns a domestic tragedy into something far grander, a mystery that captures the public imagination and casts Alicia into notoriety. The price of her art skyrockets, and she, the silent patient, is hidden away from the tabloids and spotlight at the Grove, a secure psychiatric unit in North London. Criminal psychotherapist Theo Faber is captivated by Alicia's story and jumps at the opportunity to work with her. His determination to get her to talk and unravel the mystery of why she shot her husband takes him down a path more unexpected, more terrifying than he ever imagined -- a search for the truth that threatens to consume him"-- Dust jacket
Keywords: Family violence -- Psychotherapy patients